Analisis Kualitatif Sistem Pengendalian Berkas Rekam Medis di Puskesmas Mojoagung Kabupaten Jombang - Anggun Citta Isvara Maharesi Putri; Rossalina Adi Wijayanti; Feby Erawantini; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Based on the results of a preliminary study at the Mojoagung’s Public Health Center (Puskesmas), there was matter such as the use of expedition books for the unrecorded files caused the control system for the incompatible medical record. This research aims to analyze the control system for medical record file in Puskesmas of Mojoagung, while it delivers a qualitative study by using the approach of POAC (Planning, Organizing, Actuating and Controlling). The result consists of: (a) Planning, an inappropriate control system caused by the use of unsuitable expedition books; (b) Organizing, any double jobs and unclear job description; (c) actuating, no reward and punishment for officers and no guidance on the use of expedition books; (d) controlling, no evaluation from the leadership. Therefore, there are some suggestions that researcher recommends for Puskesmas of Mojoagung as follows: applying the expedition book and evaluating routinely once three months, providing guidance to the officer to use the expedition book correctly, giving insight on the importance of using expedition books and always reminding for briefing in the morning and socialization routinely, any clear job descriptions, reward to the officer if finishing the job well and reprimand if unfinished it, briefing in each of meeting on managing medical records in particular of the control system for the medical record file, and regular meetings once a month to evaluate or assess the performance of the medical records’ officer to achieve the stated goals.